Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

dmezzullo

  • 3 years ago

Imagine you are teaching a fellow student how to solve: 4 − (x + 2) = 6 − 5(x + 4) In your own words, explain the process for solving this equation. Please include your work at each step of the process along with the final answer.

  • This Question is Closed
  1. dmezzullo
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @sirm3d

  2. dmezzullo
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @mikala1

  3. dmezzullo
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @sirm3d

  4. mikala1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    here 4 - (x +2) = 6 - 5 (x+4) --multiply through to get rid of the parenthesis 4 -x -2 = 6 -5x - 20 -- combine like terms 2 - x = -14 - 5x -- get the x's on one side -x + 5x = -14 - 2 4x = -16 x = -4 check... 4 -x - 2 = 6 - 5x - 20 4 -(-4) -2 = 6 -5(-4) - 20 4 + 4 - 2 = 6 + 20 - 20 8 - 2 = 6 6 = 6 (correct)

  5. dmezzullo
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    tyvm mik

  6. mikala1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    welcome

  7. dmezzullo
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    medal 4 me?

  8. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy